Analysis of water compartment in dengue patients - Ibrahim, Fatimah (2005)
This paper describes the water compartments in healthy subjects and dengue patients on the day of defervescence of fever using bioelectrical impedance analysis. A total of 223 healthy subjects (65 males and 158 females) and 210 dengue patients (119 males and 91 females) in Hospital Universiti Kebangsaan Malaysia (HUKM), were studied. The ages for healthy subjects vary between 14 and 60 years old with mean age of 26.05 years while the ages for the dengue patients vary between 12 and 83 years old with mean age of 30.14 years. The parameters of water compartments investigated were total body water (TBW), extracellular water (ECW) and intracellular water (ICW). There were significant difference between healthy subjects and dengue patients for both male (p<0.05) and female (p<0.001) beginning on fever day 0 till fever day 4. The mean TBW and ECW values of dengue patients obtained were found to be higher than the normal healthy subjects while the mean ICW was lower. The mean TBW and ICW for male were higher than female while the mean ECW for male was lower than female for healthy subjects and dengue patients. Â© 2005 IEEE.